2001
DOI: 10.1107/s0108767300012174
|View full text |Cite|
|
Sign up to set email alerts
|

A probabilistic approach to space-group determination from powder diffraction data

Abstract: An algorithm for the determination of the space-group symmetry of a crystal from powder diffraction data, based upon probability theory, is described. Specifically, the relative probabilities of different extinction symbols are assessed within a particular crystal system. In general, only a small number of extinction symbols are relatively highly probable and a single extinction symbol is often significantly more probable than any other. Several examples are presented to illustrate this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 3 publications
1
117
0
Order By: Relevance
“…Using positions extracted for the first 15 diffraction peaks a trigonal/ hexagonal unit-cell with dimensions of a ¼ 61:60 A, c ¼ 94:61 A was found using DICVOL [19], with figures of merit Mð15Þ ¼ 17:1 and Fð15Þ ¼ 115:9, indicating a substantially correct indexing [23]. A probabilistic approach for the space group determination [24] incorporated into DASH [25] indicated that the extinction symbol P3 1 should be chosen, giving possible chiral space groups P3 1 , P3 1 Table 1. Different structural models of the CHIKV nsP3 macro domain, native (3GPG) and complexed forms with ADP ribose (3GPO) or RNA (3GPQ) available in the PDB.…”
Section: Resultsmentioning
confidence: 99%
“…Using positions extracted for the first 15 diffraction peaks a trigonal/ hexagonal unit-cell with dimensions of a ¼ 61:60 A, c ¼ 94:61 A was found using DICVOL [19], with figures of merit Mð15Þ ¼ 17:1 and Fð15Þ ¼ 115:9, indicating a substantially correct indexing [23]. A probabilistic approach for the space group determination [24] incorporated into DASH [25] indicated that the extinction symbol P3 1 should be chosen, giving possible chiral space groups P3 1 , P3 1 Table 1. Different structural models of the CHIKV nsP3 macro domain, native (3GPG) and complexed forms with ADP ribose (3GPO) or RNA (3GPQ) available in the PDB.…”
Section: Resultsmentioning
confidence: 99%
“…3). A less subjective approach to the problem has been outlined by Markvardsen et al [14]. In this approach, all the data (i.e., the extracted correlated integrated intensities from a Pawley fit to the diffraction data) are consulted and the probabilities of each of the possible extinction symbols (consistent with the crystal symmetry) relative to the extinction symbol possessing no systematic absences, is calculated.…”
Section: Space Group Determinationmentioning
confidence: 99%
“…The diffraction pattern indexed to a monoclinic cell [M(20) = 95.7 F(20) = 253.2; DICVOL-91; Boultif & Louë r, 1991] and space group P2 1 was assigned from volume considerations and a statistical consideration of the systematic absences (Markvardsen et al, 2001). The data set was background subtracted and truncated to 59.8 2 for Pawley (1981) fitting ( 2 Pawley = 5.10) and the structure solved using the simulated annealing (SA) global optimization procedure, described previously (David et al, 1998), that is now implemented in the DASH computer program .…”
Section: Crystal Datamentioning
confidence: 99%